Studi Keanekaragaman Lichen Pada Pohon Pala, Cengkeh, Dan Coklat Di Perkebunan Rakyat Desa Ureng Kecamatan Leihitu - Kotala, Sarmawaty; Sima, Indrayani Sima; Kaliky, Nurainy; Samputri, Salma (Biosel Biology Science and Education, 2021)
Ureng village has the high biodiversity. One of which them are many groups of Lichen. This research aims was to determine the diversity of lichenes species and the diversity of thallus lichenes form in nutmeg, clove, and cocoa coffee plantation of Ureng Village. The research was done in clove, cocoa, and nutmeg of Ureng Village, Leihitu District, Maluku. The method this research was exploration method and sampling using purposive method. Lichen specimen founded was identification at MIPA IAIN Ambon Laboratory. The results this research were founded 53 species, including 19 familia. Twenty seven species lichen were found in the clove tree, 19 species are found ini the cocoa tree, 16 species found in the nutmeg tree, and 2 species found in all three trees. The results showed that the crustose type was the type of thallus lichenes that most commonly found in these plantations.